2017
DOI: 10.1039/c6ta09850a
|View full text |Cite
|
Sign up to set email alerts
|

Biomimicry of Cuscuta electrode design endows hybrid capacitor with ultrahigh energy density exceeding 2 mW h cm−2 at a power delivery of 25 mW cm−2

Abstract: Biomimicry of the Cuscutae design resulted in a supercapacitor with massive pseudocapacitive functionality implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…The intrapore V 2 O 5 ⋅H 2 O is characterized by a spongelike microtexture, which favors the infiltration of Li + throughout the 330 μm thick V 2 O 5 ⋅H 2 O/CC electrode through the numerous well‐interconnected mesopores therein. Moreover, those mesopores further buffer the volume expansion of V 2 O 5 ⋅H 2 O during charge storage to alleviate their collapse . In all, the synergistic effect accounts for the satisfactory lifespan of the α′‐Na x V 2 O 5− δ /CC//V 2 O 5 ⋅H 2 O/CC aqueous LIB developed in the present study (Figure b).…”
Section: Resultssupporting
confidence: 58%
See 3 more Smart Citations
“…The intrapore V 2 O 5 ⋅H 2 O is characterized by a spongelike microtexture, which favors the infiltration of Li + throughout the 330 μm thick V 2 O 5 ⋅H 2 O/CC electrode through the numerous well‐interconnected mesopores therein. Moreover, those mesopores further buffer the volume expansion of V 2 O 5 ⋅H 2 O during charge storage to alleviate their collapse . In all, the synergistic effect accounts for the satisfactory lifespan of the α′‐Na x V 2 O 5− δ /CC//V 2 O 5 ⋅H 2 O/CC aqueous LIB developed in the present study (Figure b).…”
Section: Resultssupporting
confidence: 58%
“…Such a porous nature endows the CC with a higher surface area than planar metallic foil. This allows this alternative current collector to be interfaced with the electroactive material more effectively . To take full advantage of this merit, V 2 O 5 ⋅H 2 O as the electroactive material with an areal mass loading of 30.63 mg cm −2 was deposited in these pore spaces (Figure c, d).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, in recent years, a lot of research work has been aimed at improving the energy densities of supercapacitors. 7,8 It has been demonstrated that nanoporous carbon materials, in particular the case of 2D carbon nanosheets with large surface area and high pore volume, are crucial to the realization of high-energy/-power supercapacitors. 9−11 Besides, based on the equation for the energy density of a supercapacitor, E = 1/2CV 2 , it is clear that the energy density is proportional to the capacitance (C) and the square of the operating voltage window (V).…”
Section: ■ Introductionmentioning
confidence: 99%